Greening the Sunnah: Authenticity, Recontextualization, and the Discursive Function of Hadith in the GreenHajj Guide - Muhammad Alvin Nur Choironi; M. Khoirul Huda (Yayasan Pesantren Mahasiswa An-Nur, 2025)
This article examines how the GreenHajj Guide, a pilgrimage manual produced by Global One 2015 and funded by Greenpeace MENA, uses prophetic tradition to authorize an environmental program. It combines two methods on a single document: takhrīj, the source-critical tracing and grading of each cited hadith, and the critical discourse analysis of van Dijk. The guide cites seven hadiths and one Qur'anic verse. The takhrīj finds that six of the seven hadiths are sound, ṣaḥīḥ or ḥasan, and correctly attributed, while one is weak and presented without its grade. The discourse analysis finds that the reports are turned toward ecology mainly through three mechanisms operating on authentic material: the resemantization of key terms, such as the rendering of al-dunyā as “earth”; the excerpting of a tradition from its context; and the literalization of figurative expression. These mechanisms cluster around the dominant frame of istikhlāf, human stewardship of a green earth. The study shows that authenticity and meaning move independently, and that a critique limited to authenticity would miss most of what the guide does.